A high-performance diaphragm slurry and a preparation method of a diaphragm thereof

CN123018351APending Publication Date: 2026-10-30ANHUI LIKE NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611254898.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种高性能隔膜浆料及其隔膜的制备方法,以解决现有锂离子电池隔膜综合性能不佳的问题

Benefits of technology

1、本发明提供的高性能隔膜浆料的呋喃基聚酰胺纳米纤维和纳米颗粒的原料可来自秸秆等农林废弃生物质,在避免了传统石油基芳纶带来的污染的同时,还大量减少碳排放,满足“双碳”政策的要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_10
    Figure SMS_10
  • Figure SMS_11
    Figure SMS_11
Patent Text Reader

Abstract

The application discloses a kind of high-performance diaphragm slurry and its preparation method of diaphragm, it is related to lithium ion battery diaphragm field.Slurry composition includes nanoparticle, nanofiber, coupling agent, dispersing agent, wetting agent, binder, solvent.The diaphragm slurry is mixed with slurry and coating process simple, can realize the coating of nanoscale coating, effectively reduce internal resistance.High-heat-resistant nanoparticle and nanofiber with furan ring structure, the structure of conjugated pi electron system and electrolyte in battery has good affinity.The glass transition temperature of binder is higher, at high temperature, binder occurs deformation, forms the isolation layer with strength, improves the safety performance of battery.Nanofiber and nanoparticle surface modification tannin form a layer of supramolecular film, enhance the dispersibility of nanofiber in water, effectively prevent its aggregation in water.The diaphragm slurry can improve the comprehensive performance of lithium ion battery to a large extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery separators, and more specifically to a high-performance separator slurry and a method for preparing the separator therefrom. Background Technology

[0002] Lithium-ion batteries are widely used in aerospace, electric vehicles, mobile devices, and energy storage systems. In recent years, with the large-scale application of lithium-ion batteries, battery performance and safety have become key concerns for users. As a crucial component of lithium-ion batteries, the separator, although not involved in electrochemical reactions, plays a vital role in ion conduction and isolating the positive and negative electrodes. Separator performance affects the battery's electrical and safety performance, thus placing high demands on separator performance. Traditional polyolefin separators suffer from poor heat resistance and insufficient wetting properties; surface coating modification technology can significantly improve their performance. Currently, mainstream slurry coatings include inorganic ceramic coatings, PVDF (polyvinylidene fluoride) coatings, and aramid coatings, but each still has significant limitations.

[0003] Inorganic ceramic coatings suffer from high internal resistance, easy detachment of ceramic particles, and rapid battery degradation during cycle life. PVDF coatings, being oil-based systems, cause severe environmental pollution. Petroleum-based aramid coatings have attracted widespread attention due to their ability to impart higher membrane breakage temperatures, lower thermal shrinkage, and better electrolyte wettability to the coated membrane. However, petroleum-based aramid coatings still face significant challenges: current petroleum-based aramid coating systems are primarily oil-based, resulting in substantial pollution and high costs. Summary of the Invention

[0004] The purpose of this invention is to provide a high-performance separator slurry and a method for preparing the separator thereon, so as to solve the problem of poor overall performance of existing lithium-ion battery separators.

[0005] The objective of this invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a high-performance diaphragm slurry, which, by mass parts, comprises the following raw materials: 10-20 parts modified nanoparticles, 10-20 parts modified nanofibers, 1-5 parts coupling agent, 1-5 parts dispersant, 0.1-0.5 parts wetting agent, 5-10 parts binder, and 50-80 parts solvent; The modified nanoparticles and modified nanofibers are obtained by modifying nanoparticles and nanofibers with tannic acid.

[0006] Furthermore, the specific steps of the tannic acid modification treatment are as follows: the nanofiber or nanoparticle dispersion is dropped into the tannic acid solution and stirred at room temperature for 12 hours.

[0007] Furthermore, the concentration of the tannic acid solution is 0.5-2 g / L.

[0008] By utilizing the phenolic hydroxyl groups and aromatic galloyl groups on tannic acid molecules, and through the synergistic effect of hydrogen bonding and π-π stacking, tannic acid is firmly and uniformly attached to the surface of nanofibers and nanoparticles. Introducing a large number of phenolic hydroxyl groups significantly enhances hydrophilicity, prevents the aggregation of nanofibers and nanoparticles, and allows the slurry to be uniformly coated onto lithium-ion battery separators, resulting in more stable separator performance after slurry coating.

[0009] Furthermore, the nanoparticles are made of furanyl polyamide and have a particle size of 0.01-0.5 μm.

[0010] Furthermore, the nanofibers are made of furanyl polyamide, with a diameter of 0.01-0.5 μm and a length of <10 μm.

[0011] Furthermore, the coupling agent is at least one of silanes, silicates, and phosphates; the dispersant is at least one of polyammonium salts, quaternary ammonium salts, and polyurethanes; and the wetting agent is at least one of polyethers and fatty alcohols.

[0012] Furthermore, the adhesive is at least one of polyimide, polyamide, polyacrylate, and polyacrylic acid, with a glass transition temperature > 200°C.

[0013] Furthermore, the solvent is deionized water.

[0014] Furthermore, the preparation method of the high-performance diaphragm slurry is as follows: S1: Prepare the raw materials according to the proportions, mix the modified nanoparticles, modified nanofibers, dispersant and solvent, and stir using a high-speed disperser to form a slurry; S2: Add coupling agent, wetting agent and binder to the slurry prepared in S1, stir using a disperser, and obtain the finished slurry after stirring.

[0015] The carboxyl or amide groups of the binder form hydrogen bonds with the amide and ether oxygen bonds on the furanyl polyamide nanofibers and nanoparticles, enhancing the stability of the coating. When the internal temperature of the battery rises, the binder in the functional coating deforms and adheres tightly to the bio-based nanoparticles and nanofibers, forming a strong insulating layer that can quickly suppress the spread of heat.

[0016] Secondly, the present invention provides a method for preparing a lithium-ion battery separator, which is prepared using the high-performance separator slurry described in any of the above-mentioned contents, and includes the following steps: coating the above-mentioned slurry onto one or both sides of a PE base film, drying and shaping to obtain a separator.

[0017] Furthermore, the above coating process is a uniform coating process, including gravure roller coating and extrusion coating.

[0018] Furthermore, the coating thickness is ≤2μm.

[0019] The beneficial effects of this invention are: 1. The high-performance diaphragm slurry provided by this invention uses furan-based polyamide nanofibers and nanoparticles as raw materials, which can be derived from agricultural and forestry waste biomass such as straw. This avoids the pollution caused by traditional petroleum-based aramids and also greatly reduces carbon emissions, meeting the requirements of the "dual carbon" policy.

[0020] 2. The modification method for furanyl polyamide nanofibers and nanoparticles provided by this invention involves forming a supramolecular layer on the surface. The core of this method lies in utilizing the phenolic hydroxyl groups and aromatic galloyl groups on tannic acid molecules as anchor points. Through the synergistic effect of hydrogen bonding and π-π stacking, these groups are firmly and uniformly attached to the surface of the nanofibers and nanoparticles. This modification introduces a large number of phenolic hydroxyl groups, significantly improving hydrophilicity and preventing the aggregation of nanofibers and nanoparticles. This allows the slurry to be uniformly coated onto the lithium-ion battery separator, resulting in more stable separator performance after slurry coating.

[0021] 3. The amide bonds and ether oxygen bonds on the furanyl polyamide nanofibers and nanoparticles provided by this invention form a hydrogen bond network with the carboxyl groups or amide groups of the binder, thereby enhancing the stability of the coating.

[0022] 4. The high-performance separator slurry provided by this invention, through the synergistic effect of a conjugated π-electron system structure formed by nanoparticles and nanofibers and a binder with a high glass transition temperature, combined with a coating process, solves the problem of poor overall performance of existing battery separators from multiple dimensions. The nanoparticles and nanofibers possess bio-based functional group furan ring structures, which can form a conjugated π-electron system structure, giving them good affinity with the electrolyte in the battery. When the internal temperature of the battery reaches a high temperature, the binder in the functional coating deforms and melts rapidly with the increasing temperature, tightly adhering to the bio-based nanoparticles and nanofibers to form a strong insulating layer that can quickly suppress the spread of heat and improve the safety performance of the battery. Furthermore, the slurry coating process forms an ultra-thin coating, reducing internal resistance and thus improving the electrical performance of the lithium-ion battery separator. Detailed Implementation

[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0024] Preparation Example 1 The synthesis method of furanyl polyamide nanoparticles is as follows: The entire reaction required nitrogen protection. Experimental equipment, solvents, and monomers were thoroughly dried and dehydrated beforehand. Under nitrogen protection, 20 g of 3,4'-diaminodiphenyl ether (ODA), 6 g of anhydrous lithium chloride, and 20 ml of pyridine were added to 150 ml of anhydrous N-methylpyrrolidone (NMP) and stirred at 40 °C until completely dissolved. The system was stabilized at -5 to 0 °C using an ice-water bath. 20 g of 2,5-furandicarboxylic acid chloride (FDCl) was dissolved in 50 ml of anhydrous NMP, and the solution was added dropwise to the reaction system, stirring for 3 h. The temperature was then slowly increased to 40 °C and maintained for 1 h to complete curing, yielding a gel. The resulting gel was added dropwise to anhydrous ethanol under high-speed stirring (800 rpm), causing precipitation. After the addition was complete, stirring continued for 0.5 h to confirm complete precipitation. After filtration using a Buchner funnel and repeated washing with hot water to remove lithium chloride, pyridine salt, and residual solvent, the product was vacuum dried at 70°C for 24 hours to obtain furanyl polyamide solid. The solid was then crushed and sieved to obtain furanyl polyamide nanoparticles with a particle size of 0.01-0.5 μm.

[0025] Preparation Example 2 The synthesis method of furanyl polyamide nanofibers includes the following steps: The entire reaction required nitrogen protection, and experimental equipment, solvents, and monomers were thoroughly dried and dehydrated beforehand. Under nitrogen protection, 20g of ODA, 6g of anhydrous lithium chloride, and 20ml of pyridine were added to 150ml of anhydrous NMP and stirred at 40°C until completely dissolved. The system was stabilized at -5 to 0°C using an ice-water bath. 20g of FDCl was dissolved in 50ml of anhydrous NMP, and the solution was added dropwise to the reaction system, stirring for 3 hours. The temperature was then slowly increased to 40°C and held for 1 hour to complete ripening, followed by vacuum drying at 70°C for 24 hours. After drying, a 9wt% spinning solution was prepared with NMP, and the solution was filtered to remove bubbles. The ambient temperature was controlled at 23°C and the humidity at 35%. Electrospinning parameters were: voltage 17kV, receiving distance 15cm, and pushing speed 0.5mL / h. The resulting long nanofibers were vacuum dried at 50°C. Long nanofibers were cut into small pieces and immersed in ice water prepared with acetic acid at pH 4.5. The mixture was then sonicated at 400W for 20 minutes in an ice-water bath, followed by high-speed shearing to break the nanofibers. After centrifugation, washing, and drying, nanofibers with a diameter of 0.01-0.5 μm and a length <10 μm were obtained.

[0026] Preparation Example 3 The modification of furanyl polyamide nanoparticles involves the following steps: 0.6 g of the nanoparticles obtained in Preparation Example 1 were ultrasonically dispersed in deionized water. The above nanoparticle dispersion was slowly added dropwise to 200 ml of a 1.5 g / L tannic acid aqueous solution. The mixture was magnetically stirred at 300 rpm for 12 h at room temperature. After the reaction was completed, the mixture was centrifuged at 3000 rpm for 5 min, and the precipitate was collected. The mixture was repeatedly centrifuged and washed with deionized water until the supernatant was clear. The precipitate was freeze-dried at -20 °C, and after 24 h, it was freeze-dried again to obtain the product.

[0027] Preparation Example 4 The modification steps for furanyl polyamide nanofibers are as follows: 0.6 g of the nanofibers obtained in Preparation Example 2 were ultrasonically dispersed in deionized water. The nanofiber dispersion was then slowly added dropwise to 200 ml of a 1.5 g / L tannic acid aqueous solution. The mixture was magnetically stirred at 300 rpm for 12 h at room temperature. After the reaction was complete, the mixture was centrifuged at 3000 rpm for 5 min, and the precipitate was collected. The mixture was then repeatedly centrifuged and washed with deionized water until the supernatant was clear. The precipitate was freeze-dried at -20 °C, and after 24 h, it was freeze-dried again to obtain the product.

[0028] Preparation Example 5 The modification of furanyl polyamide nanoparticles involves the following steps: 0.4 g of the nanoparticles obtained in Preparation Example 1 were ultrasonically dispersed in deionized water. The above nanoparticle dispersion was slowly added dropwise to 200 ml of a 1.0 g / L tannic acid aqueous solution. The mixture was magnetically stirred at 300 rpm for 12 h at room temperature. After the reaction was completed, the mixture was centrifuged at 3000 rpm for 5 min, and the precipitate was collected. The mixture was repeatedly centrifuged and washed with deionized water until the supernatant was clear. The precipitate was freeze-dried at -20 °C, and after 24 h, it was freeze-dried again to obtain the product.

[0029] Preparation Example 6 The modification steps for furanyl polyamide nanofibers are as follows: 0.4 g of the nanofibers obtained in Preparation Example 2 were ultrasonically dispersed in deionized water. The nanofiber dispersion was then slowly added dropwise to 200 ml of a 1.0 g / L tannic acid aqueous solution. The mixture was magnetically stirred at 300 rpm for 12 h at room temperature. After the reaction was complete, the mixture was centrifuged at 3000 rpm for 5 min, and the precipitate was collected. The precipitate was repeatedly centrifuged and washed with deionized water until the supernatant was clear. The precipitate was then freeze-dried at -20 °C, and the product was obtained after 24 h of freeze-drying.

[0030] Preparation Example 7 The modification of furanyl polyamide nanoparticles involves the following steps: 0.8 g of the nanoparticles obtained in Preparation Example 1 were ultrasonically dispersed in deionized water. The above nanoparticle dispersion was slowly added dropwise to 200 ml of a 2.0 g / L tannic acid aqueous solution. The mixture was magnetically stirred at 300 rpm for 12 h at room temperature. After the reaction was completed, the mixture was centrifuged at 3000 rpm for 5 min, and the precipitate was collected. The mixture was then centrifuged and washed repeatedly with deionized water until the supernatant was clear. The precipitate was freeze-dried at -20 °C, and after 24 h, it was freeze-dried again to obtain the product.

[0031] Preparation Example 8 The modification steps for furanyl polyamide nanofibers are as follows: 0.8 g of the nanofibers obtained in Preparation Example 2 were ultrasonically dispersed in deionized water. The nanofiber dispersion was then slowly added dropwise to 200 ml of a 2.0 g / L tannic acid aqueous solution. The mixture was magnetically stirred at 300 rpm for 12 h at room temperature. After the reaction was complete, the mixture was centrifuged at 3000 rpm for 5 min, and the precipitate was collected. The precipitate was repeatedly centrifuged and washed with deionized water until the supernatant was clear. The precipitate was then freeze-dried at -20 °C, and the product was obtained after 24 h of freeze-drying.

[0032] Example 1 Step 1: Prepare the raw materials according to the following mass proportions: 15 parts of modified nanoparticles prepared in Preparation Example 3, 15 parts of modified nanofibers prepared in Preparation Example 4, 3 parts of silane coupling agent KH560, 1.8 parts of polyammonium salt dispersant SN-5029, 0.2 parts of polyether wetting agent Chemadd6004, 8 parts of polyimide binder T126, and 57 parts of deionized water. Mix the modified nanoparticles prepared in Preparation Example 3, the modified nanofibers prepared in Preparation Example 4, the polyammonium salt dispersant SN-5029, and the deionized water, and stir using a high-speed disperser. After stirring for 2 hours, a slurry is formed. The high-speed disperser rotates at 2000 rpm and revolves at 20 rpm.

[0033] Step 2: Add the silane coupling agent KH560, the polyether wetting agent Chemadd6004, and the polyimide binder T126 to the slurry prepared in Step 1, and stir using a disperser. After stirring for 1 hour, the finished slurry is obtained. The disperser rotates at 600 rpm and revolves at 20 rpm.

[0034] Step 3: The finished slurry obtained in Step 2 is coated on both sides of a commercially available 7μm PE base film using a gravure roller coating process, with a coating thickness of 1μm on each side. The film is then dried and set at 80℃ to obtain the separator.

[0035] Example 2 The only difference from Example 1 is that the modified nanoparticles prepared in Example 3 were replaced with the modified nanoparticles prepared in Example 5 in equal mass proportions; and the modified nanofibers prepared in Example 4 were replaced with the modified nanofibers prepared in Example 6 in equal mass proportions. Other steps and conditions were the same as in Example 1.

[0036] Example 3 The only difference from Example 1 is that the modified nanoparticles prepared in Example 3 were replaced with the modified nanoparticles prepared in Example 7 in equal mass proportions; and the modified nanofibers prepared in Example 4 were replaced with the modified nanofibers prepared in Example 8 in equal mass proportions. Other steps and conditions were the same as in Example 1.

[0037] Example 4 The only difference from Example 1 is that the mass fraction of the modified nanoparticles prepared in Preparation Example 3 was adjusted to 10 parts, and the mass fraction of the modified nanofibers prepared in Preparation Example 4 was adjusted to 20 parts. The other steps and conditions are the same as in Example 1.

[0038] Example 5 The only difference from Example 1 is that the mass fraction of the modified nanoparticles prepared in Preparation Example 3 was adjusted to 20 parts, and the mass fraction of the modified nanofibers prepared in Preparation Example 4 was adjusted to 10 parts. The other steps and conditions are the same as in Example 1.

[0039] Example 6 The only difference between Example 6 and Example 1 is that the mass fraction of polyimide adhesive T126 is adjusted to 5 parts, while the other steps and conditions are the same as in Example 1.

[0040] Step 1: Prepare the raw materials according to the following mass proportions: 15 parts of modified nanoparticles prepared in Preparation Example 3, 15 parts of modified nanofibers prepared in Preparation Example 4, 3 parts of silane coupling agent KH560, 1.8 parts of polyammonium salt dispersant SN-5029, 0.2 parts of polyether wetting agent Chemadd6004, 5 parts of polyimide binder T126, and 60 parts of deionized water. Mix the modified nanoparticles prepared in Preparation Example 3, the modified nanofibers prepared in Preparation Example 4, the polyammonium salt dispersant SN-5029, and the deionized water, and stir using a high-speed disperser. After stirring for 2 hours, a slurry is formed. The high-speed disperser rotates at 2000 rpm and revolves at 20 rpm.

[0041] Step 2: Add the silane coupling agent KH560, the polyether wetting agent Chemadd6004, and the polyimide binder T126 to the slurry prepared in Step 1, and stir using a disperser. After stirring for 1 hour, the finished slurry is obtained. The disperser rotates at 600 rpm and revolves at 20 rpm.

[0042] Step 3: The finished slurry obtained in Step 2 is coated on both sides of a commercially available 7μm PE base film using a gravure roller coating process, with a coating thickness of 1μm on each side. The film is then dried and set at 80℃ to obtain the separator.

[0043] Example 7 The only difference between Example 7 and Example 1 is that the mass fraction of polyimide adhesive T126 is adjusted to 10 parts, while the other steps and conditions are the same as in Example 1.

[0044] Step 1: Prepare the raw materials according to the following parts by weight: 15 parts of the modified nanoparticles prepared in Preparation Example 3, 15 parts of the modified nanofibers prepared in Preparation Example 4, 3 parts of the silane coupling agent KH560, 1.8 parts of the polyammonium salt dispersant SN-5029, 0.2 parts of the polyether wetting agent Chemadd6004, 10 parts of the polyimide binder T126, and 55 parts of deionized water. Mix the modified nanoparticles prepared in Preparation Example 3, the modified nanofibers prepared in Preparation Example 4, the polyammonium salt dispersant SN-5029, and the deionized water, and stir using a high-speed disperser. After stirring for 2 hours, a slurry is formed. The high-speed disperser rotates at 2000 rpm and revolves at 20 rpm.

[0045] Step 2: Add the silane coupling agent KH560, the polyether wetting agent Chemadd6004, and the polyimide binder T126 to the slurry prepared in Step 1, and stir using a disperser. After stirring for 1 hour, the finished slurry is obtained. The disperser rotates at 600 rpm and revolves at 20 rpm.

[0046] Step 3: The finished slurry obtained in Step 2 is coated on both sides of a commercially available 7μm PE base film using a gravure roller coating process, with a coating thickness of 1μm on each side. The film is then dried and set at 80℃ to obtain the separator.

[0047] Comparative Example 1 The only difference from Example 1 is that the modified nanoparticles prepared in Example 3 were replaced with nanoparticles prepared in Example 1 in equal mass proportions; and the modified nanofibers prepared in Example 4 were replaced with nanofibers prepared in Example 2 in equal mass proportions. Other steps and conditions were the same as in Example 1.

[0048] Comparative Example 2 This comparative example prepared a ceramic-coated polyolefin membrane according to the following steps: Step 1: Prepare the raw materials according to the following proportions by weight: 30 parts boehmite ceramic powder BG-611, 3 parts silane coupling agent KH560, 1.8 parts polyammonium salt dispersant SN-5029, 0.2 parts polyether wetting agent Chemadd6004, 8 parts polyimide binder T126, and 57 parts deionized water. Mix the boehmite ceramic powder BG-611, polyammonium salt dispersant SN-5029, and deionized water, and stir using a high-speed disperser for 0.5 hours to form a slurry. The high-speed disperser rotates at 2000 rpm and revolves at 25 rpm.

[0049] Step 2: Add the silane coupling agent KH560, the polyether wetting agent Chemadd6004, and the polyimide binder T126 to the slurry prepared in Step 1, and stir using a disperser. After stirring for 1 hour, the finished slurry is obtained. The disperser rotates at 300 rpm and revolves at 25 rpm.

[0050] Step 3: The finished slurry obtained in Step 2 is coated on both sides of a commercially available 7μm PE base film using a gravure roller coating process, with a coating thickness of 1μm on each side. The film is then dried and set at 80℃ to obtain the separator.

[0051] Using the same cell materials and manufacturing processes, the separators from Examples 1-7 and Comparative Examples 1-2 were used to prepare 55Ah square wound batteries based on lithium iron phosphate, and the battery performance was tested.

[0052] Test method: Liquid absorption and retention rate test: The test diaphragm was cut into 100mm pieces. Three 100mm diaphragms were weighed and marked as m1. The diaphragms were sandwiched between two layers of lint-free cloth and rolled into a cylindrical shape, tied with a rope, and immersed in a plastic beaker containing electrolyte (1.0 mol / L lithium hexafluorophosphate, with a volume ratio of ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate of 1:1:1) for 1 hour. The diaphragms were then removed from the beaker, and the surface was quickly wiped with absorbent paper to remove the electrolyte. The weight of the wiped diaphragms was recorded as m2. The wiped diaphragms were placed in a fume hood for 1 hour and then weighed again, recorded as m3. The absorbance rate was calculated using the formula (m2 - m1) / m1. 100%, the liquid retention rate is calculated according to the formula (m3-m1) / m1 Calculate 100% and take the average of the 3 test results as the liquid absorption rate and liquid retention rate test values.

[0053] Electrolyte wetting area: A 1.0 mol / L lithium hexafluorophosphate electrolyte was used, with a volume ratio of ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate of 1:1:1. Rubber gloves were worn, and ceramic scissors / cutting knife were used to sample the diaphragm. The sample size was 100 mm. 250mm, use clamps to suspend and fix the diaphragm on the rectangular tray, ensuring that the membrane surface is free of collapse and wrinkles. Use a 25μL pipette to sample the electrolyte, drop the electrolyte vertically 10mm away from the membrane surface, time with a stopwatch, and after 1 minute, use a film ruler to measure the electrolyte wetting length in the MD / TD direction, and estimate the wetting area at the same time.

[0054] Ionic conductivity test: Cut a membrane and immerse it in an electrolyte solution of 1.0 mol / L lithium hexafluorophosphate, ethylene carbonate, methyl ethyl carbonate, and dimethyl carbonate in a 1:1:1 volume ratio, keeping it sealed and soaking for 2 hours. Inject the electrolyte into a resistance testing mold, then add one layer of membrane sequentially and test its AC impedance resistance. Repeat this process for all four layers, measuring the AC impedance resistance values ​​for each layer. During the test, ensure that the electrolyte in the resistance testing mold completely immerses the membrane. Plot a curve with the number of membrane layers on the x-axis and resistance on the y-axis, and calculate the slope and linearity of the curve. When the linearity is greater than 0.99, the curve is considered suitable according to the formula R=k 1 and σ=d / R S is used to calculate the ionic conductivity. If the linear fit is less than 0.99, the test needs to be repeated. Where: R: Resistance of one diaphragm layer, in Ω; K: The slope of the curve when the goodness of fit is greater than 0.99; σ: Ionic conductivity, unit S / cm; d: Thickness of one membrane layer, in μm; S: Diaphragm test area, in cm² 2 .

[0055] Heat shrinkage rate test: Cut the test diaphragm into 100mm pieces. Three 100mm diaphragms were used. The longitudinal and transverse lengths of each diaphragm were measured. Using a forced-air constant-temperature oven with an accuracy of ±1℃, a stainless steel plate and two pieces of quantitative filter paper were placed in the middle of the oven, with the diaphragm placed between the two filter papers. The oven door was closed, and the oven was maintained at 150℃ for 1 hour. After heating, the diaphragms were removed, and after they returned to room temperature, the longitudinal and transverse lengths were measured again. The result was calculated using the formula ΔL = (L0 - L1) / L0. The shrinkage rate was calculated using a 100% accuracy method, and the average of three test results was taken as the thermal shrinkage rate of the diaphragm. Where: ΔL: Thermal shrinkage rate, in % L0: Length before heating, in mm; L1: Length after heating, in mm.

[0056] Membrane rupture temperature test: Cut the diaphragm into strips 30cm long and 2cm wide. Use a thermomechanical analyzer with a tensile force of 0.03N and a heating rate of 5℃ / min to test from room temperature until the diaphragm breaks. Record the membrane rupture temperature as the membrane rupture temperature.

[0057] Internal resistance test: Use a resistance tester to test the prototype battery after capacity testing and record the internal resistance value of the battery.

[0058] Cycle capacity retention test: The battery was placed in a 45℃ constant temperature chamber and charged at a constant current rate of 1C until the termination voltage was reached, then switched to constant voltage charging. Charging was stopped when the charging current dropped to 0.05C. After resting for 30 minutes, the battery was discharged at a 0.5C rate. After resting for another 30 minutes, the charging process was repeated. This cycle was repeated 500 times. The battery discharge capacity / initial capacity was then measured. 100% calculation of capacity retention rate.

[0059] Thermal runaway test: The battery was tested by increasing the temperature in stages from 50°C using an adiabatic accelerated calorimeter. After each 3°C increase, the battery was allowed to stand for 1 hour before the temperature was increased to 300°C. The battery status was recorded at the end of the test.

[0060] The membrane performance of Examples 1-7 and Comparative Examples 1-2 was tested, and the results are shown in Table 1: Table 1

[0061] Battery performance tests were conducted on Examples 1-7 and Comparative Examples 1-2, and the results are shown in Table 2: Table 2

[0062] As shown in Tables 1 and 2, compared to Comparative Examples 1-2, the membranes in Examples 1-7 all exhibit relatively higher liquid absorption rate, liquid retention rate, electrolyte wetting area, ionic conductivity, and lower internal resistance. This is because the nanoparticles and nanofibers in these examples possess a furan ring structure, which can form a conjugated π-electron system, resulting in better affinity between the membrane and the electrolyte in the battery. Furthermore, through tannic acid modification, the nanofibers and nanoparticles exhibit better dispersibility in water, are less prone to agglomeration, have a more uniform slurry coating, and exhibit more stable membrane performance.

[0063] Furthermore, as shown in Tables 1 and 2, the separators in Examples 1-7 exhibit superior safety performance. This is because when the internal temperature of the battery reaches a high level, the binder in the functional coating deforms and melts rapidly with increasing temperature, bonding tightly with the nanoparticles and nanofibers to form a strong insulating layer. This layer can quickly suppress the spread of heat and improve the battery's safety performance.

[0064] Of Examples 1-3, Example 1 showed the best performance because Example 2 had a lower tannin concentration and Example 3 had an excessively high concentration. The lower concentration resulted in insufficient phenolic hydroxyl groups, leading to suboptimal dispersion of the nanofibers and nanoparticles in water and unstable membrane performance. The excessively high concentration caused pore blockage and fiber adhesion, resulting in decreased membrane performance.

[0065] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0066] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A high-performance diaphragm slurry, characterized in that, The slurry comprises the following raw materials by weight: 10-20 parts modified nanoparticles, 10-20 parts modified nanofibers, 1-5 parts coupling agent, 1-5 parts dispersant, 0.1-0.5 parts wetting agent, 5-10 parts binder, and 50-80 parts solvent; The modified nanoparticles and modified nanofibers are obtained by modifying nanoparticles and nanofibers with tannic acid.

2. The high-performance diaphragm slurry according to claim 1, characterized in that, The specific steps of the tannic acid modification treatment are as follows: the nanofiber or nanoparticle dispersion is dropped into the tannic acid solution and stirred at room temperature for 12 hours.

3. The high-performance diaphragm slurry according to claim 2, characterized in that, The concentration of the tannic acid solution is 0.5-2 g / L.

4. The high-performance diaphragm slurry according to claim 1, characterized in that, The nanoparticles are made of furanyl polyamide and have a particle size of 0.01-0.5 μm.

5. The high-performance diaphragm slurry according to claim 1, characterized in that, The nanofibers are made of furanyl polyamide, with a diameter of 0.01-0.5 μm and a length of <10 μm.

6. The high-performance diaphragm slurry according to claim 1, characterized in that, The coupling agent is at least one of silanes, silicates, and phosphates; the dispersant is at least one of polyammonium salts, quaternary ammonium salts, and polyurethanes; and the wetting agent is at least one of polyethers and fatty alcohols.

7. The high-performance diaphragm slurry according to claim 1, characterized in that, The adhesive is at least one of polyimide, polyamide, polyacrylate, and polyacrylic acid, with a glass transition temperature >200℃.

8. The high-performance diaphragm slurry according to claim 1, characterized in that, The solvent is deionized water.

9. The high-performance diaphragm slurry according to claim 1, characterized in that, The method for preparing the slurry is as follows: S1: Prepare the raw materials according to the proportions, mix the modified nanoparticles, modified nanofibers, dispersant and solvent, and stir using a high-speed disperser to form a slurry; S2: Add coupling agent, wetting agent and binder to the slurry prepared in S1, stir using a disperser, and obtain the finished slurry after stirring.

10. A method for preparing a diaphragm, characterized in that, The preparation of the diaphragm using the high-performance slurry as described in any one of claims 1-9 includes the following steps: coating the slurry onto one or both sides of a PE base film, drying and setting it to obtain the diaphragm.